Merekonstruksi Paradigma Gugatan Citizen Lawsuit Di Indonesia Sebagai Sengketa Administrasi - Bimasakti, Muhammad Adiguna (Jurnal Hukum & Pembangunan, 2020)
Citizen Lawsuit is an alternative law enforcement mechanism for citizens. Every citizen has the same right to file a Citizen Lawsuit in the court. However, the problems are that there is no definite regulation regarding the authority to adjudicate Citizen Lawsuit, and its contact with the “Judicial Review” which is the constitutional authority of the Supreme Court. In addition there are also problems related to discretionary authority where there is a prohibition for judges to judge the good and bad of the government's discretionary actions. This paper tries to answer these problems through normative and theoretical approaches. The contact between Judicial Review and Citizen Lawsuit is that if the object is an existing regulation. Prohibition for judges from assessing the good and bad of the government's discretionary action can be ruled out as long as the assessment is made regarding purposes of discretionary actions ruled under Law No. 30 of 2014 concerning Government Administration. The character of Citizen Lawsuit is administrative, not civil, so it should be the authority of the State Administrative Court and not the General Court to adjudicate.